Summary of Structure and performance of Ethiopia’s coffee export sector - Minten, Bart; Tamru, Seneshaw; Kuma, Tadesse; Nyarko, Yaw (International Food Policy Research Institute, 2014)
We study the structure and performance of the coffee export sector in Ethiopia, Africa’s most important coffee producer, over the period 2003 to 2013. We find an evolving policy environment that leads to structural changes in the export sector, including an elimi-nation of vertical integration for most exporters. Ethiopia’s coffee export earnings increased four-fold in real terms over this period. This increase has mostly been due to changes in international market prices. The quality of coffee improved only slightly over this time, but the quantity exported increased by 50 percent, explained by both higher domestic supplies and reduced local consumption. To further progress coffee export performance, investments to increase the quantities produced and to improve quality are needed, including an increase in washing, certification, and traceability, as these characteristics are shown to be associated with significant quality premiums in international markets.